Evaluation Of Street Children Program In Children Care Community NGO In Kampung Aur Medan - Elvira Destia (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2021)
Street children are one of the most common social problems facing each country in the world. Street children are divided into three, namely: children who have economic activities as child labor on the street, but still have a strong relationship with their parents. Children who participate fully in the streets, both socially and economically. Children from families living on the streets. This study aims to describe the achievement of coaching program objectives through NGO KOPA for street children in Kampung Aur. To know the supporting and inhibiting factors of coaching program through NGO KOPA for street children in Kampung Aur. Since Kampung Aur is located in a densely populated area on the banks of the Deli River, the urban poor condition has many problems with children's background, such as the problem of street children and children in trouble with their families. The approach used in this research is descriptive qualitative with data collection method is observation / observation, documentation, and interview. The data already collected will be presented by reducing unnecessary data in the study. After that done withdrawal of conclusion / verification. Based on the results of research, the program runs well although not too significant, it's just still have deficiencies in the inputs, namely human resources, facilities and also insufficient funds. After that done withdrawal of conclusion / verification. Based on the results of research, the program runs well although not too significant, it's just still have deficiencies in the inputs, namely human resources, facilities and also insufficient funds. After that done withdrawal of conclusion / verification. Based on the results of research, the program runs well although not too significant, it's just still have deficiencies in the inputs, namely human resources, facilities and also insufficient funds.